Peningkatan Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu Dengan Model Pembelajaran Kooperatif Tipe Picture and Picture di Sekolah Dasar - Putri Humairah; Zuardi Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this study was to improve student learning outcomes in thematic learning integrated with the Picture And Picture model in class II elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were teacher and students of  II grades were 26. Research conducted in two cycles. The research procedure includes planning, implementation, observation, and reflection.The results showed that : a) the Average RPP cycle I 81,77% (Good) dam cycle II 97,72% (Very Good ) b) the Average of the conduct on the aspect of teacher cycle I 87,49% (Good) and Cycle II 95,83% (Very Good ) c) the Average Execution on the aspects of the student Cycle I 79,16% (Enough) and Cycle II 95,83% (Very Good) d) the Average student learning outcomes Cycle I 77,73% (Enough) and Cycle II 88,59 (Good). Thus the model Kooperatif Tipe Picture and Picture can improve learning outcomes Thematic Integrated students of class II SDN 01 Benteng Pasar Atas kota BukittinggiKeywords: Cooperative Picture and Picture Type, Learning Outcomes, Integrated Thematic